2002
DOI: 10.1002/pssc.200390109
|View full text |Cite
|
Sign up to set email alerts
|

Direct, Independent Measurement of Twist and Tilt Mosaic as a Function of Thickness in Epitaxial GaN

Abstract: The twist and tilt mosaics in a series of GaN epitaxial films grown by metal-organic vapour-phase epitaxy (MOVPE) have been measured directly by grazing incidence in-plane X-ray diffraction and in the standard symmetric high resolution setting. The variation in tilt mosaic with layer thickness fits well the model of Ayers. A similarly good fit to the same function for the twist mosaic dependence on epilayer thickness is found, indicating that the ratio of edge to screw dislocations remains constant for all fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…On the other hand, the same tendency of the tilt and the twist mosaic evolution versus epilayer thickness was found in Ref. [15]. In our case, where GaN layers are grown with the SiN treatment method, we noted that the thickness has a more pronounced effect on the twist mosaic than on the tilt as illustrated by its smaller slope.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…On the other hand, the same tendency of the tilt and the twist mosaic evolution versus epilayer thickness was found in Ref. [15]. In our case, where GaN layers are grown with the SiN treatment method, we noted that the thickness has a more pronounced effect on the twist mosaic than on the tilt as illustrated by its smaller slope.…”
Section: Resultssupporting
confidence: 81%
“…To check the reliability of the extrapolated values, GIIXD was used for the direct measurement of in plane twist mosaic. The method was successfully used in previous works [14][15][16]. Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The crystallinity of the LED structures is analyzed in terms of the mosaic crystal model [9][10][11]. The broadening of symmetric, (00.2), (00.4), and (00.6), and asymmetric (10.2), (10.3), (10.4), (10.5), reflexes from GaN obtained by X-ray ω-scan has been used to estimate screw and edge threading dislocations density, respectively [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…However, previous X-ray studies have shown that there are ,5 times as many edge dislocations in this sample as screw dislocations. 31 It therefore must be concluded that -at least for the authors' particular imaging geometry -any contrast owing to the presence of edge dislocations is considerably less than that for screw dislocations. It is observed that small changes of tilt angle produce significant changes in the contrast of the observed dislocations.…”
Section: Resultsmentioning
confidence: 98%